Validation of the Chinese Cultural Tightness–Looseness Scale and General Tightness–Looseness Scale - Leng, Jie; Ma, Hang; Lv, Xiaojun; Hu, Ping (Frontiers in Psychology, 2023)
Introduction This study aims to revise the Cultural Tightness–Looseness Scale (CTLS) and General Tightness–Looseness Scale (GTLS), and explore the group heterogeneity of tightness–looseness perception in Chinese populations. Methods Sample 1 (n = 2,388) was used for item analysis and exploratory factor analysis, and sample 2 (n = 2,385) was used for confirmatory factor analysis and latent profile analysis. Sample 3 (n = 512) was used for the reliability test and criterion validity test, among which 162 participants were used for the test–retest reliability examination after a four-week interval. Measurements included the CTLS, GTLS, International Personality Item Pool, Personal Need for Structure Scale, and Campbell Index of Well-Being. Results The revised CTLS contained four items and retained a single-dimensional structure. The revised GTLS consisted of eight items divided into two dimensions: Compliance with Norms and Social Sanctions. Latent profile analysis extracted two profiles on both CTLS and GTLS scores, indicating that the sample can be divided into two subgroups: high and low perception of tightness. Discussion The Chinese versions of the CTLS and GTLS can be used as valid and reliable measures of tightness–looseness perception in a Chinese population.